2022
DOI: 10.3389/fphar.2022.935685
|View full text |Cite
|
Sign up to set email alerts
|

Identification of naturally occurring inhibitors in Xian-Ling-Gu-Bao capsule against the glucuronidation of estrogens

Abstract: Xian-Ling-Gu-Bao (XLGB) capsule, a well-known traditional Chinese medicine prescription, is widely used for the treatment of osteoporosis. It could significantly increase the levels of estrogen in ovariectomized rats and mice. However, this working mechanism has not been well elucidated. Considering that UDP-glucuronosyltransferase (UGT) enzymes are the important enzymes that inactivate and regulate estrogen activity in vivo, this study aimed to identify the bioactive compounds from XLGB against the glucuronid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…XLGB, a well-known traditional Chinese medicine prescription, is known for its effects in nourishing yin and blood, promoting blood circulation, resolving blood stasis, regulating the immune system, and enhancing bone density (He et al, 2022). Numerous studies have found that XLGB has a variety of active ingredients, including flavonoids, terpenes, and phenylpropanoids, etc., (Guan et al, 2011;Tang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…XLGB, a well-known traditional Chinese medicine prescription, is known for its effects in nourishing yin and blood, promoting blood circulation, resolving blood stasis, regulating the immune system, and enhancing bone density (He et al, 2022). Numerous studies have found that XLGB has a variety of active ingredients, including flavonoids, terpenes, and phenylpropanoids, etc., (Guan et al, 2011;Tang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…BuGuZhi is popularly used in the treatment of patients with inflammatory diseases or malignancy at late stages 6–8 . CYA had been reported to exhibit inhibitive effects on glucuronidation of estrogens, 9 STAT3 activation 10 as well protective effects against ionizing radiation injury 11 and dexamethasone‐induced muscle atrophy 12 . However, the effects of CYA on cancer cachexia have not been reported before.…”
Section: Introductionmentioning
confidence: 99%